Best practices, challenges and innovations in pediatrics in 2019 - Carlo Caffarelli; Francesca Santamaria; Angelica Santoro; Michela Procaccianti; Fabio Castellano; Francesca Fiori Nastro; Alberto Villani; Sergio Bernasconi; Giovanni Corsello (BMC, 2020)
Abstract This paper runs through key progresses in epidemiology, pathomechanisms and therapy of various diseases in children that were issued in the Italian Journal of Pediatrics at the end of last year. Novel research and documents that explore areas such as allergy, critical care, endocrinology, gastroenterology, infectious diseases, neonatology, neurology, nutrition, and respiratory tract illnesses in children have been reported. These observations will help to control childhood illnesses.